The Random House book of poetry for children - Lobel, Arnold; Prelutsky, Jack. (New York : Random House, 1983)
More than 550 poems by American, English, and anonymous authors.
"Opening poems for each section especially written for this anthology by Jack Prelutsky."
Includes indexes.
Book Links (A.L.A.)
Wilson's Children
Wilson's Junior High School
2.2
Keywords: Children's poetry, American; Children's poetry, English; American poetry -- Collections; English poetry -- Collections; American poetry -- Collections; English poetry -- Collections